Penanaman Karakter Kejujuran Dan Kepatuhan Pada Aturan Sosial Dalam Proses Pembelajaran Ppkn Di Smk Muhammadiyah 2 Surakarta Tahun 2015-2016 - Sari, Triana Kartika, Dra. Sundari, SH., M.Hum (2016)
The objective of this research is to describe the character building of honesty and obedience to social rules in the learning process of Civics Education in SMK Muhammadiyah 2 Surakarta. This study is a qualitative research. The data is collected through observation, interviews, and documentation. To validate the data, the researcher uses data triangulation sources and data collection techniques. Meanwhile, to analyze the data, the researcher uses interactive analysis techniques. The results of this study indicate that: Honesty building in the learning process of Civics Education is familiarized by telling the truth from early age, taking a test or daily quiz honestly without cheating, teaching not to lie by means telling the truth in everyday activities. Obedience building in social rules in the learning process of Civics Education is implemented by the teacher should give an example to the students in advance in an orderly manner to obey the rules of teachers / employees. The obstacle in building honesty in the learning process of Civics Education is the students tendency to lie if they are asked whether they understand the lesson or no. The obstacle in building obedience in social rules in the learning process of Civics Education is there are some students who are late for school because of oversleep, and students tend to cluster with each group. The solutions in building honesty in the learning process of Civics Education is the teacher should be a role model for students by providing example of honest attitude which will be responded by the students to imitate the honesty, in order to motivate them not to cheat. The solutions for building obedience in social rules in the learning process of Civics Education is by giving motivation and forming a heterogeneous learning group to enable students to manage themselves from the surrounding environment, especially in the class, while to make students obey the rules of the school, they must be taught that there are punishments as punishment education.